Contemporary epidemiological landscape of pediatric non-Hodgkin lymphoma: a global burden of disease analysis - Luo, Xiaobo; Xie, Pin; Zhou, Min; Xia, Yi; Gao, Yu; Li, Hui (Frontiers in Oncology, 2025)
IntroductionThis study evaluated the distribution characteristics, influencing factors, and future trends of non-Hodgkin lymphoma (NHL) burden in children and adolescents globally from 1990 to 2021.MethodsData were obtained from the Global Burden of Disease Study database. Multiple analytical methods were used, including Joinpoint regression, age-period-cohort analysis, decomposition analysis, frontier analysis, health equity analysis, and Bayesian age-period-cohort (BAPC) model.ResultsIn 2021, the global age-standardized prevalence rate was 3.177/100,000, with a disability adjusted life year (DALY) rate of 13.535/100,000. The prevalence demonstrated a fluctuating downward trend during 1990-2021. Age, period, and cohort effects significantly influenced disease patterns. While population growth drove prevalence increase, population aging and epidemiological factors had negative impacts. Disease burden showed a non-linear negative correlation with Socio-demographic Index (SDI). Over the past nearly 30 years, health inequality has intensified, as some African regions have shown relatively low prevalence rates due to limited resource Settings, which have restricted disease diagnosis and reporting, compared with the developed areas with high prevalence. The BAPC model predicted further decrease from 2022-2036.DiscussionDespite overall decline, significant regional differences and health inequalities persist, suggesting future focus on targeted prevention, optimized resource allocation, and improved treatment.